Pre-intervention child maltreatment risks, intervention engagement, and effects on child maltreatment risk within an RCT of MHealth and parenting intervention - Baggett, Kathleen M.; Davis, Betsy; Olwit, Connie; Feil, Edward G. (Frontiers in Digital Health, 2023)
Although the most effective interventions for preventing future child maltreatment strengthen parent practices that protect against maltreatment before occurrence, most child maltreatment intervention services are delivered primarily after harm has occurred. Evidence-based mental health and parenting support services for mothers postpartum can reduce risk for child maltreatment. However, women suffering economic and cultural stressors disproportionately shoulder the burden of infant caregiving while experiencing profound barriers to accessing mental health and parenting services. Addressing child maltreatment risk for these mothers of infants is crucial given that the highest risk for child maltreatment, compared to all other developmental periods, occurs during infancy, the most rapid period of neurodevelopment in the lifespan. Digital MHealth and positive parenting support interventions have potential to overcome service access barriers in the first year postpartum. This article reports on an mHealth and parenting intervention targeting maternal mood and positive parent practices within a randomized controlled trial. The sample of 184 predominantly Black mothers and their infants provided a unique opportunity to view pre-intervention child maltreatment risk, its relationship to subsequent intervention engagement, and intervention engagement effects on pre-post child maltreatment risk reduction. Pre-intervention child maltreatment risk did not differentiate subsequent maternal intervention completion patterns. Mothers who completed majority of intervention, compared to those who did not, demonstrated significant reductions in pre-post child maltreatment risk. Findings underscore promise of mobile interventions to reduce substantial child maltreatment risk through service delivery addressing mental health and parenting needs postpartum, a particularly vulnerable developmental period for maternal depression and child maltreatment.